Editorial: Muslim World Current Issues - Editor Al-Jami'ah: Journal of Islamic Studies (Al-Jami'ah Research Centre, 2006)
Globalisation has proofed its self as a very spectacular phenomenon until no one may deny its impacts, but on the other hand, it reflexively suggests localization of the global. In this context, religion is not exclusion. It remains believed however, that religion still has its formula for solving the problems that emerged from globalisation. Scholars have devoted attempts to propose new ideas for this challenge. Local interpretations of symbols representing “global” Islam, for instance, increasingly grow in line with the growth of Islamic revival. This has drawn very much attention and responses from Muslims, whether to protest against or support for the new idea. The present edition of the journal is designed to more deeply explore the current issues from Muslim world, whether as very local phenomena or in a more global context.